(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
Peripartum cardiomyopathy (PPCM) is a rare but potentially lethal complication of pregnancy occurring in approximately 1in 3000 live births in the United States although some series report a much higher incidence. African-American women are particularly at risk. Diagnosis requires symptoms of heart failure in the last month of pregnancy or within five months of delivery in the absence of recognized cardiac disease prior to pregnancy as well as objective evidence of left ventricular systolic dysfunction. Obstetricians should suspect the diagnosis, particularly if the patient has risk factors. Evaluation should include an echocardiogram to assess the LV systolic function. Treatment includes ACE inhibitors or angiotensin receptor blockers, beta-blockers, and diuretics. Consideration should be given to anticoagulation. A number of causes are being investigated, including nutritional, infectious, and genetic, which, hopefully, lead to more targeted treatments. This paper provides an updated, comprehensive review of PPCM, including emerging insights into the etiology of this disorder as well as current treatment options. Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 67-70 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8531